2008
DOI: 10.1016/j.jvs.2008.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Endarterectomy vs stenting for carotid artery stenosis: A systematic review and meta-analysis

Abstract: In RCTs, carotid stenting and carotid endarterectomy seem equivalent in terms of death and nonfatal myocardial infarction. Although the impact on stroke remains unestablished, results are consistent with a clinically important increase in stroke risk with stenting, an intervention that aims at reducing the risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 30 publications
1
45
0
5
Order By: Relevance
“…These results suggest that endarterectomy has more favorable effects on periprocedural and long-term outcomes and should remain the treatment of choice for patients with carotid stenosis. Although our periprocedural results are similar to those of previous studies, [27][28][29] to our knowledge, our meta-analysis is the first to include the long-term results from Brooks et al, 22 EVA-3S, 15 and the International Carotid Stenting Study (ICSS). 26 With the inclusion of these recently available data, our meta-analysis has produced more precise estimates than those of previous studies in this area, including a previous Cochrane review by Bonati et al 30 (odds ratio for long-term stroke and periprocedural death, 1.39; 95% CI, 1.10-1.75).…”
Section: Discussionsupporting
confidence: 86%
“…These results suggest that endarterectomy has more favorable effects on periprocedural and long-term outcomes and should remain the treatment of choice for patients with carotid stenosis. Although our periprocedural results are similar to those of previous studies, [27][28][29] to our knowledge, our meta-analysis is the first to include the long-term results from Brooks et al, 22 EVA-3S, 15 and the International Carotid Stenting Study (ICSS). 26 With the inclusion of these recently available data, our meta-analysis has produced more precise estimates than those of previous studies in this area, including a previous Cochrane review by Bonati et al 30 (odds ratio for long-term stroke and periprocedural death, 1.39; 95% CI, 1.10-1.75).…”
Section: Discussionsupporting
confidence: 86%
“…458 Other meta-analyses found CAS to be inferior to CEA or associated with higher rates of periprocedural stroke. [613][614][615] In another meta-analysis of 11 trials that included 4796 patients (10 of which reported on short-term outcomes [nϭ4709] and 9 of which reported on intermediate-term outcomes, or 1 to 4 years), the risk of periprocedural mortality or stroke was lower with CEA than with CAS (OR 0.67, 95% CI 0.47 to 0.95; Pϭ0.025). This was based mainly on a lower risk of stroke (OR 0.65, 95% CI 0.43 to 1.00; Pϭ0.049), because the risk of death (OR 1.14, 95% CI 0.56 to 2.31; Pϭ0.727) and the composite endpoint of mortality or disabling stroke (OR 0.…”
Section: Meta-analyses Comparing Carotid Endarterectomy and Stentingmentioning
confidence: 99%
“…[29][30][31][32][33] Murad et al 29 used a random-effects meta-analysis to evaluate the death, stroke (disabling and non-disabling), and nonfatal MI rates at 30 days in 10 randomized controlled trials representing 3182 patients. They based equivalency of the 2 procedures on an absolute difference in events of ,2%.…”
Section: Discussionmentioning
confidence: 99%